1993
DOI: 10.1002/qre.4680090309
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in quality—A baseline for achieving total quality management

Abstract: Interest in comprehensive concepts, such as lean enterprises, time‐based competition and total quality management, has increased significantly within the engineering industry in recent years. Successful implementation of those concepts can to a large extent be explained by the ability to get information across to the employees and to make them involved and committed. Earlier research has shown that one of the key factors behind the successful implementation of changes in the quality area is to create clear goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…We have in our study found indications that this is a factor at least partly in play when it comes to implementing the ISO system in industry. Earlier studies have shown an extremely large discrepancy between the way in which company management and employees perceive and interpret quality strategies [14]. To remedy this situation, a possible way forward might be greater member participation through delegation of the operative quality work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have in our study found indications that this is a factor at least partly in play when it comes to implementing the ISO system in industry. Earlier studies have shown an extremely large discrepancy between the way in which company management and employees perceive and interpret quality strategies [14]. To remedy this situation, a possible way forward might be greater member participation through delegation of the operative quality work.…”
mentioning
confidence: 99%
“…More efficient routines ought, in all probability, to lead to improvements in terms of scrap, quality deficiency costs as well as lead times and productivity. Earlier studies have emphasized the difficulty of understanding the linkage between higher quality and improved productivity [14].…”
mentioning
confidence: 99%
“…High prices increase consumers’ desire to acquire high utility and quality (Lim & Dubinsky, 2004). High quality can be measured by consistent performance, which drives consistent cues or inferences (Carlsson, 1993). Therefore, when CRD exists for higher‐priced merchants, consumers are more likely to generate negative perceptions, such as disappointment and anxiety, when their expectations of high quality are not met (Zeelenberg & Pieters, 2004).…”
Section: Hypothesis Developmentmentioning
confidence: 99%